Use of pulsed electron avalanche knife (PEAK) PlasmaBlade™ in patients undergoing implantation of subcutaneous implantable cardioverter-defibrillator. (September 2019) - Kaya, Elif; Siebermair, Johannes; Azizy, Obayda; Dobrev, Dobromir; Rassaf, Tienush; Wakili, Reza
Abstract: Introduction: Surgical implantation of subcutaneous implantable cardioverter-defibrillators (S-ICD) requires preparation of a deeper and larger pocket. Infection and bleeding complications are reported, particularly in patients requiring antiplatelet therapy (APT) or being on oral anticoagulation (OAC), with rates up to 25%. The pulsed electron avalanche knife (PEAK) PlasmaBlade™ has been reported to reduce bleeding complications. The purpose of this study was to evaluate the safety and feasibility of a PEAK guided S-ICD implantation with respect to perioperative complications. Methods and results: We enrolled 36 consecutive patients (75% male; mean age 52.1 ± 14.4 years) undergoing S-ICD implantation. Periprocedural safety endpoints comprised major complications including pocket hematomas, wound infections, bleeding (BARC ≥2) or events requiring interventions. Patients were divided into three groups according to management of their anticoagulation: i.) APT, n = 15 (41.7%); ii.) OAC, n = 10 patients (27.8%); iii.) none (neither OAC nor APT), n = 11 (30.6%). Mean procedure duration was 33.1 ± 13.4 min. Mean length of hospital stay was 3.3 ± 2.1 days. Overall analysis showed no differences between the 3 groups with respect to major complications, major bleeding episodes or other procedural parameters, beside a trend towards more minor hematomas in the OAC group (OAC: 22.2% vs. APT: 11.4% vs. none: 9.1%; p  = 0.15). Conclusion: The results of our pilot study suggest that intermuscular S-ICD implantation using PEAK is safe and potentially beneficial in patients receiving OAC or APT with respect to prevention of bleeding complications. These results support the rationale for large prospective controlled trials evaluating a beneficial effect of PEAK use in S-ICD implantation procedures.